2010
DOI: 10.1111/j.1365-2109.2010.02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of myostatin-like genes expressed highly in the muscle tissue from Morotoge shrimp, Pandalopsis japonica

Abstract: Myostatin is one of the transforming growth factor (TGF)‐β family members and plays inhibitory roles in the development and growth of muscle in mammals. Mammalian myostatins have been studied intensively, considering its medical and industrial potential use. Still, limited information is available about myostatin homologues in crustaceans. In the present study, we isolated for the first time cDNA that encodes for myostatin‐like protein (Pj‐MSTN) from Morotoge shrimp, Pandalopsis japonica. The putative mature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
1
18
2
Order By: Relevance
“…It stands to reason that a combined functional role of the iMstn/Gdf11 gene may be reflected in a broader tissue gene expression profile, one that is less specialized than that of the vertebrate Mstn or Gdf11 paralogs. Indeed, transcripts of the pmMstn/Gdf11 gene were expressed in a wider variety of shrimp tissues, including muscle, gills, heart, eyestalk and hepatopancreas, similar to the expression observed in other crustaceans such as P. japonica, G. lateralis and H. americanus (Covi et al, 2008;Kim et al, 2010;MacLea et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It stands to reason that a combined functional role of the iMstn/Gdf11 gene may be reflected in a broader tissue gene expression profile, one that is less specialized than that of the vertebrate Mstn or Gdf11 paralogs. Indeed, transcripts of the pmMstn/Gdf11 gene were expressed in a wider variety of shrimp tissues, including muscle, gills, heart, eyestalk and hepatopancreas, similar to the expression observed in other crustaceans such as P. japonica, G. lateralis and H. americanus (Covi et al, 2008;Kim et al, 2010;MacLea et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Loss-offunction mutations of the MSTN gene in vertebrates result in heavily muscled phenotypes (McPherron and , whereas increasing circulating levels of MSTN induces muscle atrophy (Ma et al, 2003;Shao et al, 2007;Wehling et al, 2000). Recently, invertebrate orthologs of genes similar to Mstn have been reported in a number of species, including decapod crustaceans (Covi et al, 2008;Covi et al, 2010;Kim et al, 2010;MacLea et al, 2010); however, the function of these gene orthologs has not been specifically investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to a study on the characterization of the role of MSTN specifically in the aquaculture sector as muscle regeneration in crustaceans is believed to be closely associated with the molting process (Saravanan, Kamalam, & Kumar, ). In crustaceans, MSTN is reported to regulate the molting process as the ablation of the X‐organ/sinus gland complex downregulates the expression of MSTN in most tissues in Pandalopsis japonica (Kim et al, ), and high MSTN expression is observed in skeletal muscle during the intermolt stage in Gecarcinus lateralis (Covi, Kim, & Mykles, ). Most studies have demonstrated the functional role of MSTN in crustaceans on the basis of changes in MSTN gene regulation, but further studies are required to distinguish its role in the regeneration process as established in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Mstn may also regulate muscle growth in invertebrates. cDNAs encoding Mstnlike proteins have been characterized in mollusks and arthropods (Covi et al, 2008;De Santis et al, 2011;Hu et al, 2010;Kim et al, 2004;Kim et al, 2009;Kim et al, 2010;Lo and Frasch, 1999;MacLea et al, 2010). In blackback land crabs (Gecarcinus lateralis), molt-induced atrophy and unweighting atrophy have opposite effects on Gl-Mstn expression in claw closer and thoracic muscles, respectively.…”
mentioning
confidence: 99%